Occurrence and ecological risks of organochlorine pesticides and polychlorinated biphenyls in a semi-enclosed urban watershed - Chidewe, Liberty; Zhang, Rongrong; Shi, Xizhi; Zhang, Zeming (Frontiers in Marine Science, 2025)
Organochlorine pesticides (OCPs) and polychlorinated biphenyls (PCBs) are pollutants of global concern due to their toxicity, bioaccumulation, and long-term ecological consequences in marine ecosystems. Their presence and associated hazards were investigated in the water–sediment system of the Xiangshan Harbour Watershed, a zone influenced by both industrial and agricultural activities. Samples were obtained from 19 key locations during autumn (October 2020) and summer (July 2021). OCP concentrations ranged from 0.03–231.52 ng/L in water and 0.28–804.27 μg/kg in sediment, while PCBs ranged from 0.01–7.35 ng/L in water and 0.35–3.77 μg/kg in sediment. The lower section of the XianXiang River (XX-DOWN) was the hotspot for OCPs, and the Huangduan Harbor lower section (HDG-DOWN) was the hotspot for PCBs. Temperature and salinity were positively correlated with pollutant concentrations. Source identification using diagnostic ratios indicated OCPs mainly originated from lindane and technical DDT, while PCA–MLR analysis showed PCBs were sourced from e-waste (15.3%), thermoplastics (57.1%), and pigments (27.6%). Risk quotient (RQ) analysis revealed ecological risks from hexachlorobenzene, PCB 138, and DDT metabolites. Total non-carcinogenic hazard quotient (TnHQ) values remained below 1 for all assessed age groups—infants, children, teens, and adults—indicating low risks. Continuous surveillance along with targeted pollution control strategies in the watershed are encouraged.